Ovarian Steroid Cell Tumor (Not Otherwise Specified): A Case Report of Ovarian Hyperandrogenism - Hadjkacem Faten; Ghorbel Dorra; Charfi Slim; Safi Wajdi; Charfi Nadia; Chaabene Kais; Boudawara Tahia; Abid Mohamed (Case Reports in Oncological Medicine)
Steroid cell tumors (SCTs) (not otherwise specified (NOS)) are rare sex cord-stromal tumors of the ovary. These are associated with hormonal disturbances resulting in menstrual bleeding patterns and androgenic effects. We report the case of a 36-year-old female presented with hirsutism, signs of virilization, and elevated androgen levels. Transvaginal ultrasound showed a solid-appearing right ovarian mass. She underwent fertility-sparing surgery with a laparoscopic left oophorectomy. Histological examination showed a benign steroid cell tumor, NOS. These tumors often small can then present a problem of positive diagnosis responsible for a delay in the diagnosis.